Biodegradation of the gasoline oxygenates methyl tert-butyl ether, ethyl tert-butyl ether, and tert-amyl methyl ether by propane-oxidizing bacteria. - Steffan, R J (1997)
Several propane-oxidizing bacteria were tested for their ability to degrade gasoline oxygenates, including methyl tert-butyl ether (MTBE), ethyl tert-butyl ether (ETBE), and tert-amyl methyl ether (TAME). Both a laboratory strain and natural isolates were able to degrade each compound after growth on propane. When propane-grown strain ENV425 was incubated with 20 mg of uniformly labeled [14C]MTBE per liter, the strain converted > 60% of the added MTBE to 14CO2 in < 30 h. The initial oxidation of MTBE and ETBE resulted in the production of nearly stoichiometric amounts of tert-butyl alcohol (TBA), while the initial oxidation of TAME resulted in the production of tert-amyl alcohol. The methoxy methyl group of MTBE was oxidized to formaldehyde and ultimately to CO2. TBA was further oxidized to 2-methyl-2-hydroxy-1-propanol and then 2-hydroxy isobutyric acid; however, neither of these degradation products was an effective growth substrate for the propane oxidizers. Analysis of cell extracts of ENV425 and experiments with enzyme inhibitors implicated a soluble P-450 enzyme in the oxidation of both MTBE and TBA. MTBE was oxidized to TBA by camphor-grown Pseudomonas putida CAM, which produces the well-characterized P-450cam, but not by Rhodococcus rhodochrous 116, which produces two P-450 enzymes. Rates of MTBE degradation by propane-oxidizing strains ranged from 3.9 to 9.2 nmol/min/mg of cell protein at 28 degrees C, whereas TBA was oxidized at a rate of only 1.8 to 2.4 nmol/min/mg of cell protein at the same temperature.